Novas estratégias para avaliação de pessoas com deficiências pulmonares crônicas - Liliane Patricia de Souza Mendes (2019)
The World Health Organization recommends the use of the International Classification of Functioning, Disability, and Health (ICF) to comprehensively assess individuals with different health conditions. The classification considers health domains and health-related domains and is described on the basis of body functions and structure, activity, and participation. The inclusion of activities and participation considers the whole health experience, rather than a limited focus on aspects of the diseases. A patient-centred outcome assessment thus, should measure all domains including impairments in body functions and structure, limitations to activities and restrictions of participation in order to consider the whole health experience of the individual. Thus good evaluation tools should be available to assess impairments, detect activity limitations and identify participation restrictions. This thesis evaluates new approaches to assess people with chronic pulmonary disabilities in all ICF domains. In this context, Chapter 1 provides a summary of comprehensive assessments of functioning in health conditions, particularly chronic obstructive pulmonary disease (COPD), which is the focus of this thesis. Chapter 2 presents a literature review of three important areas to be assessed in people with chronic pulmonary disabilities, based on the ICF domains of body function and structure, activity, and participation, which are the pattern of breathing, functional capacity, and functional performance, respectively. This chapter also presents methods of measurement of breathing pattern, functional capacity and functional performance. In Chapter 3, the pattern of breathing of 168 healthy participants in age ranges from 21 to 91 years was assessed using optoelectronic plethysmography with the aim of developing reference values, which have not been previously established. The study developed reference values for males and females for each ten-year increment in age for individuals aged from 20 to 59 years, and also a reference value for those aged 60 years and above. These reference values will be important for comparison and better understanding of the alterations of these variables in individuals with different respiratory impairments that may compromise respiratory function. Chapter 4 presents modifications to a test of functional capacity, the Glittre-ADL test. This test requires participants to perform a series of daily activities while wearing a weighted backpack, which may affect balance. The study in this chapter evaluated the Glittre-ADL test with and without a backpack in a randomised crossover study design. There were no differences between the tests with and without the backpack in physiological response and symptoms, except for upper limb fatigue that was reported by males as significantly higher for the test performed with the backpack. In addition, the Glittre-ADL test performed without the backpack was responsive to change following a pulmonary rehabilitation program. Further modifications of the Glittre-ADL test are presented in Chapter 5. The outcome of the test is the time taken to complete five laps of the test, however previous studies have observed that oxygen consumption reached a plateau after the third lap. These findings suggest that the Glittre-ADL test might be adequately performed in three laps instead of five laps. The study in Chapter 5 aimed to compare the differences in performance of the Glittre-ADL test with and without the backpack in three and five laps in people with COPD. The main findings of this study were that the three lap Glittre-ADL test both with and without the backpack provoked the same symptoms and oxygen desaturation as the 5-lap test, except for heart rate that was significantly higher for the 5-lap test, and that the tests were responsive to change following a pulmonary rehabilitation program. In chapter 6, a new test of endurance capacity for functional activities, the Glittre Endurance test, was developed and evaluated. The rationale for developing an endurance test was that endurance tests, such as the endurance shuttle walk test, have been shown to be more sensitive to change after interventions like pulmonary rehabilitation compared to the incremental shuttle walk test or the six-minute walk test. This is because people with COPD after a pulmonary rehabilitation program often cannot significantly improve the speed with which they perform activities, but may be able to perform activities for longer, with less breathlessness and fatigue. In order to evaluate endurance capacity for daily activities, 52 participants with COPD were recruited to develop and evaluate the Glittre Endurance test. The main findings were that a Glittre Endurance test was developed which showed a learning effect when a second Glittre Endurance test was performed; the Glittre Endurance test time did not correlate with the outcomes of any other field tests; and that the Glittre Endurance test was responsive to change following a pulmonary rehabilitation program. The study in Chapter 7 evaluated the relationship between functional capacity (measured by the Glittre-ADL tests with and without the backpack and the Glittre Endurance test) compared with daily physical activity measured by an accelerometer worn for seven days. The study aimed to determine which Glittre tests best represented daily physical activity in people with COPD. The main findings were that Glittre-ADL test time correlated moderately with number of steps and time spent in moderate activities; Glittre-ADL test time performed without the backpack time was moderately correlated with number of steps; Glittre Endurance test time was moderately correlated with number of steps per day and moderately correlated with time spent in vigorous activities. Chapter 8 integrates the main findings of the studies within the thesis and provides clinical implications of the findings and suggestions of areas for future research.